Ultrastructure of the uterus, embryonic envelopes and the coracidium of the enigmatic tapeworm Tetracampos ciliotheca (Cestoda: Bothriocephalidea) from African sharptooth catfish (Clarias gariepinus) - Yoneva, Aneta; Kuchta, Roman; Smit, Nico (Parasitology research, 2020)
Transmission electron microscopy (TEM) was used to study the ultrastructure of the uterus and egg morphology in the enigmatic bothriocephalidean tapeworm Tetracampos ciliotheca. The uterine wall, underlain by well-developed muscle bundles, consists of a syncytial epithelium which is characterized by the abundance of free ribosomes, mitochondria and cisternae of granular endoplasmic reticulum (GER). On the apical surface of the uterine epithelium, there is an abundant network of cytoplasmic microlamellae projecting into the uterine lumen. The lumen is filled with freely lying eggs which are located close to the uterine wall but do not contact with the microlamellae of the uterine epithelium. The developed eggs possess an oncosphere surrounded by four envelopes: (1) a thin egg shell; (2) an outer envelope; (3) a syncytial, ciliated inner envelope; and (4) the oncospheral membrane. The mature hexacanth is armed with three pairs of oncospheral hooks, as well as somatic and hook muscles and five types of cells (1) binucleated subtegumental cell, (2) somatic cells, (3) penetration gland cells, (4) nerve cells and (5) germinative cells. Considering the relative scarcity of descriptive and comparative studies on the ultrastructure of the uterus and egg morphology in the order Bothriocephalidea, we concluded that Tet. ciliotheca displays a unique type of egg development. Based on these results, we discuss plausible ideas relating to the function of these structures for consideration in future studies.
Keywords: Cestoda; Oncosphere; Ovum; ovum; Fish Diseases; cestodózy; Bothriocephalidea; Uterus; TEM; uterus; Egg; Catfishes; larva; Animals; ženské pohlaví; Microscopy, Electron, Transmission; zvířata; nemoci ryb; Evolution; Larva; Female; sumci; Cestode Infections; transmisní elektronová mikroskopie